Determinantes econômicas do consumo de energia elátrica no Estado do Ceará - Miranda, Luiz Antonio Trotta (2004)
The increase of electric power consumption is considered one of the basic conditions for the economic growth of any country. Brazil, in the last years, has presented significant increases in its supply/demand of electric power, in spite of the Federal Government having lack of financial resources to invest adequately in this sector. Nevertheless, the country has experienced sharp modifications in its energy structure, trying to adjust itself to guarantee the future of the sector and sustain the country growth. To properly know how to estimate the demand for electric power, through econometrical analyses, it is to be considered of high importance to a country or a region development. It allows private investor to supply the deficiency of investments of the public sector. This work will use several econometrical models, by the method of the least square and the method of the two stages least square to suggest models that explain the consumption path of electric power in the State of the Ceará The econometric analyses considered, as independent variables: the number of domiciles of the State of Ceará, the GGP of the State of Ceará and Brazil, the average Brazilian energy tariffs, the Brazilian electric power consumption, and a qualitative dummy variable. It was done 07 different models using the least square method and 02 models using the two stages least square method. Each model was then individually analyzed. Some variables that initially were given credit to have high representation in the power consumption of the state, as for example the tariffs of electric power, had been demonstrated during the work little significance in many models, while others, such as the number of domiciles, had showed high significance in the models. That’s the main reason why it was opted to make a large variety of models, allowing to analyze the interaction of all the variables. For the method of the two stages least square, it was considered as endogenous variables the GGP of the State of the Ceará and consumption de electric power of the State of Ceará.